Hydrophilic Cu3BiS3 Nanoparticles for Computed Tomography Imaging and Photothermal Therapy. (29th January 2015) - Yang, Yan; Wu, Huixia; Shi, Benzhao; Guo, Linlin; Zhang, Yingjian; An, Xiao; Zhang, Hao; Yang, Shiping
<x xml:space="preserve">Abstract</x> Hydrophilic Cu3BiS3 nanoparticles (NPs) have been prepared using the thermal decomposition of precursor complexes in oily‐mixed solvent followed by coating the produced Cu3BiS3 NPs with polyvinylpyrrolidone (PVP). The resulting Cu3BiS3/PVP NPs remain stable in aqueous solutions over a long period of time, and meanwhile, they show low in vitro cytotoxicity and negligible toxicity to mice in vivo. Cu3BiS3/PVP NPs could operate as an efficient dual‐modal contrast agent to simultaneously enhance X‐ray computed tomography imaging and photothermal imaging of tumor model in vivo. Moreover, highly efficient ablation of cancer cells both in vitro and in vivo has been successfully achieved by combining Cu3BiS3/PVP NPs with near‐infrared (NIR) laser irradiation. All of the positive results in this study highlight that Cu3BiS3/PVP NPs could serve as a promising platform for cancer diagnosis and therapy.